Plate 3: Blowpipes; apparatus for producing phosphoric acid - Accum, Friedrich Christian (An Explanatory Dictionary of the Apparatus and Instruments Employed in the Various Operations of Philosophical and Experimental Chemistry, 1824)
Depicts assorted blowpipes (self-adjusting candlestick; oxy-hydrogen), compound distillatory apparatus, furnace, and an apparatus for the production of phosphoric acid in figure 9.
Keywords: Chemistry; Chemical apparatus